RTTBD‐like activity in association with hippocampal ictal discharges in patients with temporal lobe epilepsy. Issue 4 (19th September 2020) - Sun, Taixin; Liu, Xi; Issa, Naoum P.; Rose, Sandra; Wu, Shasha; Wang, Qun; Martinez, Raisa; Towle, Vernon L.; Jr, Douglas R. Nordli; Warnke, Peter; Tao, James X.
Abstract: Aim . To determine clinical and intracranial EEG correlates of rhythmic temporal theta bursts of drowsiness (RTTBD) and assess its clinical significance in patients with temporal lobe epilepsy (TLE). Methods . A retrospective review of simultaneous scalp and intracranial video‐EEG recordings from 28 patients with TLE was evaluated for epilepsy surgery. Scalp RTTBD patterns were identified and their clinical and intracranial EEG correlates were then determined on video‐EEG recording using depth and subdural electrodes. Results . Thirty‐one RTTBD patterns on scalp EEG were observed in six (21%) of the 28 patients. Five (16%) of the RTTBD patterns occurred during wakefulness and 26 (84%) occurred during drowsiness and light sleep. The mean duration of RTTBD was 10 seconds (range: 3‐28 seconds). RTTDB consistently correlated with hippocampal ictal discharges and was time‐locked to the hippocampal seizures in which the ictal discharges evolved into rhythmic theta frequency (4‐7‐Hz) range. Ictal automatisms were observed during five (16%) RTTBD patterns, while cognitive impairment was observed in four (13%) of the 31 RTTBD patterns. Conclusion . Our findings show that scalp EEG correlates of hippocampal ictal discharges can resemble RTTBD and may be associated with ictal symptoms and cognitive impairment, indicating that RTTBD may rarely be an ictal EEG pattern in patients with TLE.